Robida’s Mormons - Daryl Lee (Transatlantica)
Nineteenth-century French observers fascinated with the American West appropriated cultural aspects of the region in a variety of ways. This transnational exchange included “Mormons,” members of the Church of Jesus Christ of Latter-day Saints who migrated progressively west from the Missouri and Illinois frontiers in the 1830s and 40s to the Great Basin after 1847, where they established an extensive network of colonies. Author-illustrator Albert Robida depicted the “polygamist sect” in venues such as Le Journal amusant and La Caricature, and in two novels, his Jules Verne-inspired Voyages très extraordinaires de Saturnin Farandoul (1879) and the futuristic satire Le Vingtième siècle (1883) set in 1953. In the latter, Robida conflated orientalist stereotypes abounding in accounts of Mormon polygamy and in French salon painting, by removing the Mormons from the Rocky Mountains and transplanting them to Europe in order to think through French preoccupations with geopolitics, colonization, and the role of women in society.